The 7-step “P” technique: a novel manual push method for high-quality OCT imaging in severe coronary stenosis - Jincheng Guo; Saiying He; Jia Zhou; Hao Liu; Zixuan Li; Zijing Liu; Senhu Wang; Haotian Wang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAchieving optimal optical coherence tomography (OCT) imaging in patients with severe coronary stenosis is challenging because of the catheter-induced restriction of distal contrast flushing within the lesion.AimsTo evaluate the effectiveness of manual contrast injection followed by OCT catheter advancement in improving image clarity in patients with severe coronary stenosis.MethodsThis single-centre observational study included 60 patients with acute coronary syndrome who demonstrated antegrade thrombolysis in myocardial infarction (TIMI) flow ≥2 on coronary angiography before the OCT catheter was passed through the severe coronary lesions. Catheter advancement resulted in TIMI 0–1 flow. A 7-step “P” technique was developed and implemented to optimise OCT imaging clarity, using manual contrast injection followed by catheter advancement distal to the region of interest (ROI). Image quality was evaluated using a semi-quantitative scoring system to assess the number of quadrants (0–4) in which the vessel walls were clearly visualised.ResultsA total of 1,722 OCT frames were meticulously analysed, with a mean ROI length of 18.99 ± 8.82 mm. This technique consistently produced high-quality images with an average quality score of 3.88 ± 0.38. The proximal lesion segment generally showed a slightly higher image quality compared to the distal segment, with both regions achieving reasonably high clarity scores (3.90 ± 0.28 vs. 3.85 ± 0.45, p < 0.001), though the clinical relevance of this difference is minimal. No complications occurred.ConclusionsThe 7-step “P” technique with manual injection is a safe and effective method for acquiring high-quality OCT images in patients with severe coronary artery stenosis, offering a practical alternative in clinical practice.